The rate of complicated appendicitis during a nonpharmaceutical intervention in two territories with different COVID-19 incidence - Bauci, Gabriele; Arigoni, M.; Passoni, S.; Ukegjini, K.; Marti, Lukas; Steffen, T. (BMC gastroenterology, 2025)
Background: During the COVID-19 pandemic, many worldwide governmental agencies implemented non-pharmaceutical interventions (NPIs) to contain its spread. Many general surgeons reported higher rates of complicated appendicitis in this period. Reports in the literature need to be more consistent. This study aimed to compare the rates of complicated appendicitis in two Swiss territories with very different COVID-19 incidences during the first lockdown period. Methods: We performed a retrospective two-center cohort analysis in two Swiss territories during the first wave of the COVID-19 pandemic in 2020. We compared the rates of complicated acute appendicitis during the lockdown period from March to June 2020 to those during the pre-pandemic period in 2019. The rate of complicated appendicitis was the primary endpoint. Results: A total of 393 patients were identified. More patients (215, 55%) were operated on in the pre-pandemic period, compared to 178 (45%) during the COVID-19 pandemic. The rate of complicated appendicitis during the lockdown period was significantly higher than in previous years (39% vs. 28%) (p = 0.021). We found a significant increase from 17% to 32% (p = 0.024) in the highly affected region of Ticino. In patients under 20 years old, the rate of complicated appendicitis increased from 12% to 47% (p = 0.016). The median time to admission in Ticino was significantly higher during the lockdown period compared to both pre-pandemic period and the area of St. Gallen (p < 0.001). Conclusion: A higher rate of complicated appendicitis was found in the region most affected by the COVID-19 pandemic. NPIs in a pandemic situation, such as a lockdown period or restricted access to health services, leads to higher morbidity in patients with acute appendicitis.